Pengaruh Penyuluhan Kesehatan Terhadap Pengetahuan Remaja Tentang Hiv/Aids Di Sman 14 Kota Bekasi - Ayu Syifa Zhafira Basuki; Teti Oktianingsih; Dayuningsih Dayuningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
HIV/AIDS remains a public health problem that requires serious attention, particularly among adolescents who are vulnerable due to limited knowledge and limited access to health information. School are strategic setting for improving knowledge and preventing HIV/AIDS through health education. This study aimed to determine the effect of health education on adolescents’ knowledge of HIV/AIDS at SMAN 14 Bekasi City. This quantitative study with a pre-experimental one group pre-test and post-test design. A total of 91 respondents were selected using cluster random sampling. Data were collected using an HIV/AIDS knowledge questionnaire administered before and after the health education intervention. Data analysis was performed using the Wilcoxon Signed Rank Test with a significance level of 0.05. The mean knowledge score increased from 8.31 in the pre-test to 19.59 in the post-test, with a p-value < 0.05. Health education had a significant effect on improving adolescents’ knowledge of HIV/AIDS and should be implemented continuously in school setting.